Recombinant human C1 esterase inhibitor treatment for hereditary angioedema attacks in children. Issue 5 (29th May 2019) - Reshef, Avner; Grivcheva‐Panovska, Vesna; Kessel, Aharon; Kivity, Shmuel; Klimaszewska‐Rembiasz, Maria; Moldovan, Dumitru; Farkas, Henriette; Gutova, Vaclava; Fritz, Stephen; Relan, Anurag; Giannetti, Bruno; Magerl, Markus
Abstract: Background: Attacks of hereditary angioedema (HAE) due to C1 esterase inhibitor deficiency (C1‐INH‐HAE) usually begin during childhood or adolescence. However, limited data are available regarding indications and modalities of treatment of children. This study evaluated recombinant human C1‐INH (rhC1‐INH) for HAE attacks in children. Methods: This open‐label, phase 2 study included children aged 2‐13 years with C1‐INH‐HAE. Eligible HAE attacks were treated intravenously with rhC1‐INH 50 IU/kg body weight (maximum, 4200 IU). The primary end‐point was time to beginning of symptom relief (TOSR; ≥20 mm decrease from baseline in visual analog scale [VAS] score, persisting for two consecutive assessments); secondary end‐point was time to minimal symptoms (TTMS; <20 mm VAS score for all anatomic locations). Results: Twenty children (aged 5‐14 years; 73 HAE attacks) were treated with rhC1‐INH. Seventy (95.9%) of the attacks were treated with a single dose of rhC1‐INH. Seven (35.0%) children were treated for four or more attacks. Overall, median TOSR was 60.0 minutes (95% confidence interval [CI], 60.0‐65.0); data were consistent across attacks. Median TTMS was 122.5 minutes (95% CI, 120.0‐126.0); data were consistent across attacks. No children withdrew from the study due to adverse events. No treatment‐related serious adverse events or hypersensitivity reactions were reported; no neutralizing antibodies were detected. Conclusions: Recombinant human C1‐INH was efficacious, safe, and well tolerated in children. Data support use of the same dosing regimen for HAE attacks in children (50 IU/kg; up to 4200 IU, followed by an additional dose, if needed) as is currently recommended for adolescents and adults.